2004
DOI: 10.1017/s1461145704004407
|View full text |Cite
|
Sign up to set email alerts
|

A multivantaged behavioural method for measuring onset and sequence of the clinical actions of antidepressants

Abstract: An aim in development of new antidepressants (ADs) now includes increasing speed of action. New drugs are tested primarily in outpatients who are less severely depressed than the patients treated in earlier trials of the tricyclic drugs. To determine early efficacy requires measures sensitive to initial changes in components of the illness as well as in the severity of the entire syndrome of depression. This paper describes the development of a brief 'multivantaged' (MV) method for assessing the major behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The analyses in this proof-of-concept study were conducted on the study data described in detail in Katz et al 2 To determine whether a large scale study was feasible, it required a randomized control study of a new drug, designed to include a representative clinical sample of patients' conditions diagnosed as MDD, one or more comparative drugs, a placebo control, a multicomponent profile (multivantage [MV]) of assessed changes 11 including the Ham-D, 6 and assessment conducted on a weekly basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses in this proof-of-concept study were conducted on the study data described in detail in Katz et al 2 To determine whether a large scale study was feasible, it required a randomized control study of a new drug, designed to include a representative clinical sample of patients' conditions diagnosed as MDD, one or more comparative drugs, a placebo control, a multicomponent profile (multivantage [MV]) of assessed changes 11 including the Ham-D, 6 and assessment conducted on a weekly basis.…”
Section: Methodsmentioning
confidence: 99%
“…To test whether 2 weeks is sufficient to decide on the drug's efficacy, the proportion of "early improvers" (EIs) (ie, patients who show a ≥20% decrease shown by Stassen et al 1 to be significant clinical improvement) in the Ham-D total or on a major dimension of the disorder at 2 weeks is sufficiently high to ensure that 65% or more of patients will show a positive response to the new drug at the 6-or 8-week outcome on (1) the Ham-D total and/or (2) a major dimension of the disorder (ie, anxiety-agitation, depressed mood, hostility). 11,12 To preserve the integrity of the 6-to 8-week trial, the "interim" analysis at 2 weeks, however, would have to be conducted by a statistician independent of the conduct of the trial, thus preserving the required double blind. The 2-week analysis, therefore, would not determine whether 20% or more early improvement was sustained throughout the trial, as required by the definition by Stassen.…”
mentioning
confidence: 99%
“…Quitkin et al (1984a, b) and Quitkin and Stewart (1984) introduced a pattern analysis that identified persistent and non-persistent response and early and delayed onset of activity and the combination of these two, response level and onset patterns. Expectations of an early antidepressant effect from responder groups also changed the timing of data collection in clinical trials from weekly to 3 day or even more frequent intervals (for in-depth discussion of these approaches see reviews by Katz et al, 2002Katz et al, , 2004a). An analysis of the impact of effect measurement frequency on apparent drug AOT was conducted by Mallinckrodt et al (2006) who used a categorical repeated measures approach and a traditional assessment schedule, and found frequent estimates beneficial for data evaluation.…”
Section: Methods Used To Assess Activity Onset Time For Drugs In Clinmentioning
confidence: 99%
“…There is no consensus on the best model to determine AOT. The results presented are controversial with some papers arguing for an onset delay of antidepressant drug activity and others for almost immediate activity (for review see Katz et al, 1987Katz et al, , 1996Katz et al, , 2004aKatz et al, , b, 2006Stassen et al, 1993Stassen et al, , 1996Derivan, 1995;Muller and Moller, 1998;Thompson, 2002). There is also no consensus of what onset of activity means.…”
Section: Introduction: Definition Of Drug Activity Onset Timementioning
confidence: 99%
“…Methods to measure the components are available (see example, earlier work by Katz et al 18 and Raskin et al 19 ).…”
Section: The Scientific Evidence Of Early Clinical Actions and Implicmentioning
confidence: 99%